Perspektif Disabilitas dalam Pemilu 2014 dan Kontribusi Gerakan Difabel Indonesia bagi Terbangunnya Pemilu Inklusif di Indonesia - Ishak Salim (Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract : This paper seeks to analyze how the contribution of Disability Social Movements in Indonesia to improve the quality of the future elections. The author is one of the organizers of this movements and follow the processes of disabled community organizing during the elections in four regions: Makassar (South Sulawesi), Balikpapan (East Kalimantan), Bantul (Yogyakarta), and Situbondo (East Java). Two things that are the focus of my analysis are the results of a survey on the perception of legislative candidates in 4 regions and election monitoring by Sasana Integrasi dan Advokasi Difabel (SIGAB) and its partners (Disabled people Organizations in a number of districts). The results of this survey and monitoring both contribute to the political science, especially in introducing Disability Perspectives in Electoral and Party Systems. In the present of political science study in Indonesia, scientists are relatively still do not understand yet the disability perspective in their efforts to develop a disability-based research methods and further designing a number of political instruments, in particular the way a difabel choosing political actors who cares for the disabled intersets and designing election models. The survey results indicate that the capacity of knowledge and experience the legislators candidate on the issue of disability is still weak, then how are we supposed to fill this lack of knowledge of disability through cooperation between political parties and organizations with a disability principal approach - agency. While the results of the election monitoring conducted by disabled people organizations have contributed to the explanation of how the election should take place and to accommodate the interests of voters with disabilities. Exposure results of this research and monitoring simultaneously aims to improve the quality of parliamentarians, election administration, and the electoral system so that political practice can take place in inclusion and more meaningful.Keywords: Disabilities Perspective, General Elections, Inclusiveness; Difabel; Difabel Organization